2011
DOI: 10.1080/09084282.2010.523392
|View full text |Cite
|
Sign up to set email alerts
|

A Canonical Correlation Analysis of Intelligence and Executive Functioning

Abstract: Executive functioning is one of the most researched and debated topics in neuropsychology. Although neuropsychologists routinely consider executive functioning and intelligence in their assessment process, more information is needed regarding the relationship between these constructs. This study reports the results of a canonical correlation study between the most widely used measure of adult intelligence, the Wechsler Adult Intelligence Scale, 3rd edition (WAIS-III; Wechsler, 1997), and the Delis-Kaplan Execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
2
20
0
2
Order By: Relevance
“…As a result, other researchers (Lezak et al, 2004;Reynolds & Horton, 2008) would view these reassigned skills as components of executive functioning. This is consistent with research by Davis et al (2011) that indicates measures of executive functioning have unique sources of variance that are not attributable to Gf or Gc.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…As a result, other researchers (Lezak et al, 2004;Reynolds & Horton, 2008) would view these reassigned skills as components of executive functioning. This is consistent with research by Davis et al (2011) that indicates measures of executive functioning have unique sources of variance that are not attributable to Gf or Gc.…”
supporting
confidence: 89%
“…In part, this is due to the difficulty and disagreement between researchers as to the key features of executive functioning and which instruments best measure those constructs (Davis, Pierson, & Finch, 2011;Delis, Kaplan, & Kramer, 2001;Salthouse). Executive functioning has historically primarily been anatomically associated with the functioning of the prefrontal cortex.…”
mentioning
confidence: 99%
“…Increasing age is also accompanied by a decline in complex cognitive functioning indexed by some frontal tests (Kemp, Després, Sellal, & Dufour, 2012; Lamar & Resnick, 2004; MacPherson et al, 2002) and also general fluid intelligence ( g f ; Deary et al, 2009; Salthouse, 2004). Despite the interest that differential psychologists and neuropsychologists share in the frontal lobes of the brain and how they age, there are few comparisons of scores from the tests produced by these two areas of psychology (Davis, Pierson, & Finch, 2011). It is important to capture all aspects of cognitive ageing if we are to understand its nature and determinants, but two key issues of validity levelled at frontal tests (Rabbitt, Lowe, & Shilling, 2001) have significantly hampered research on this issue in the cognitive ageing literature: vagueness of conceptual boundaries and uniqueness of theoretical construct.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salthouse (2005) and Davis et al (2011) both highlight the lack of consensus regarding definitions of ‘executive function’ and the diversity of methods used to assess it. Rabbitt (1997) observed that the common usage of ‘inhibition’ perpetuates misleading analogies between potentially unrelated functional processes.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical correlation specifically examines the relations among multiple continuous dependent and independent variables when there is no covariate (Tabachnick & Fidell, 2007). It is used when directional relationships may not be expected, and allows for the simultaneous estimation of both correlation between sets of variables and to determine how much each variable within the sets contributes to the observed relation (Davis, Pierson, & Finch, 2011). Rejecting the null hypothesis for this analysis indicates that the sets of variables are related.…”
Section: Methodsmentioning
confidence: 99%